2019
DOI: 10.1111/cch.12709
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver creation of participation‐focused care plans using Participation and Environment Measure Plus (PEM+), an electronic health tool for family‐centred care

Abstract: Background Family‐centred care (FCC) is a model for rehabilitation practice that focuses on collaborative partnerships between providers and clients (i.e., children and their caregivers). FCC is a best‐practice standard and is expected to yield better outcomes for children and greater caregiver satisfaction with rehabilitation services. A commonly cited barrier to implementing FCC is perceptions about caregiver capability to contribute to designing an initial plan of care, due to lack of skill and/or interest.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…In rehabilitation, goal-setting has become an integral part of the therapy process across professions, including pediatric participation–focused interventions [ 133 , 134 ]. Previous research has shown that caregivers can be guided to create participation-focused goals on the web [ 149 ]. Including goal-setting in AI-supported pediatric rehabilitation interventions might be an important first step to enable tailoring interventions to the participation needs of children and youth with disabilities or other diagnosed health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In rehabilitation, goal-setting has become an integral part of the therapy process across professions, including pediatric participation–focused interventions [ 133 , 134 ]. Previous research has shown that caregivers can be guided to create participation-focused goals on the web [ 149 ]. Including goal-setting in AI-supported pediatric rehabilitation interventions might be an important first step to enable tailoring interventions to the participation needs of children and youth with disabilities or other diagnosed health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We will rate EI service plans using quality rating criteria, 16 54 to derive estimates of the proportion of participation-focused goals before and after intervention. We will control for history of family interview completion (yes, no) to examine the effect of the upgraded YC-PEM e-PRO and decision support tool on the proportion of participation-focused goals in the EI service plan.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The information in this report can integrate with standardised processes used to facilitate IFSP meetings, thereby helping to further structure provider-parent communication around intervention priorities and goal attainment strategies. [16][17][18][19] The YC-PEM e-PRO holds promise in improving EI service quality in two ways: (1) expediting and expanding EI provider reach for family-centred and participationfocused service design in partnership with individual families; and (2) aggregating the YC-PEM e-PRO data to examine trends in participation over time as a function of EI service use for groups of families. 13 20 21 It is therefore a promising electronic health systems intervention to strengthen the parent-practitioner relationship and equip programmes with a common data element for conducting robust patient-centred outcomes research to drive quality improvement efforts.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The subtheme service coordination, organization and structure emphasized the importance of activities such as responding to initial concerns (Robinshaw & Evans, 2001), accessible supports and resources (Chong et al, 2012) and coordinated care (Nickbakht et al, 2019). Care planning and goal setting revealed the importance of formal administrative processes such as Individualized Family Service Plans (IFSPs) (Bosak et al, 2019) and clear guidelines/ protocols (Carter & Thomas, 2011) in the provision of FCC, especially in newer publications. Similarly, Routines-Based Interviewing was employed as a means of setting functional and meaningful child and family goals (Ridgley et al, 2020).…”
Section: Processes Of Fccmentioning
confidence: 99%